A degree That Includes Vocational Education Textbooks of the Higher Basic Level in Jordan for Reproductive Health Concepts - Al- Lahham, Mervat Fakhry; Abu Sneina, Odeh Abdel- Jawad (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the degree of inclusion of reproductive health concepts in the vocational education subject for the higher basic stage in Jordan, by analyzing the content of these books, the tool represented in building a list of reproductive health concepts that included (18) domains and (42) concepts that were applied to a sample of four vocational education books. The reliability coefficient of the tool was (92.2%).And the study adopted the descriptive- analytical approach. The results of the study revealed that the vocational education book for the tenth grade was the most inclusive of reproductive health concepts, with a percentage of (46.2%) of the total repetitions in four books, and this percentage falls within a high degree of inclusion. The vocational education book for the ninth grade came in the second rank with a rate of (23.5%), and this value is considered as a low degree of inclusion. In the third rank was the vocational education book for the seventh grade at a rate of (17.9%) which is considered a low degree of inclusion also. While the vocational education book for the eighth grade came in the fourth and last, with a rate of (12.4%), which is considered a low degree of inclusion too. As the number of reproductive health, concepts found in the vocational education books for the high basic stage reached 19 concepts, while the four vocational education books together did not include the remaining 23 concepts of reproductive health. It came in the following domains: marriage, genetic diseases, pregnancy, abortion, childbirth, breastfeeding, sexually transmitted diseases, and diseases related to the male and female reproductive system. The study recommended including the concepts of reproductive health included in the vocational education books in low percentages or those not mentioned in the vocational education books for the high basic stage.